Effect of Ethiopian kaolin treatment on the performance of adsorptive removal of methylene blue dye - Wondimhun Tedila Sibhat; Hailu Sheferaw Ayele; Minaleshewa Atlabachew; Kedir Seid Mohammed; Belete Asefa Aragaw; Bamlaku Abebaw; Dessie Tibebe Ayele (Results in Chemistry)
Textile industries discharge significant amounts of effluents containing synthetic dyes, raising public concern. This study investigates the effectiveness of kaolin, a naturally abundant clay mineral, and its derivatives in adsorbing methylene blue (MB) dye from aqueous solutions. Ethiopian natural kaolin was processed mechanically, wet, chemically, and thermally to yield a variety of kaolin adsorbents in the forms of raw (RK), beneficiated (BK), acid-leached (ALK), and calcined (CK). Characterization techniques such as PHzpc, XRD, FTIR, BET for characterizing samples and UV–Vis Spectrophotometry were employed to analyze the adsorption process. The characterization results show the change in surface property, crystallinity, and porosity during treatment of raw kaolin. The effects of adsorbent dose (0.2–1 g), pH (3–11), starting MB concentrations (20–100 mg/L), temperature (30–70 °C) and contact duration (20–100 min) were evaluated in batch adsorption studies. Maximum dye removal efficiencies of 99 %, 99.84 %, 99.76 %, and 100 % were achieved for RK, BK, CK, and ALK, respectively, under optimal conditions of 20 mg/L MB, 30 °C, 60 min contact time, pH 9, and 1 g/100 mL adsorbent. From the thermodynamic data it was observed that the process was most efficient at lower temperatures, indicating that adsorption is more feasible and exothermic at these conditions. All kaolin adsorbents demonstrated over 90 % removal efficiency, with more than 90 % retention after five reuse cycles, showcasing their stability and reusability. Acid leaching produced a more effective kaolin adsorbent compared to thermal and wet treatments.